2021
DOI: 10.1596/1813-9450-9700
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Impacts of SPS and TBT Regulations: Firm-Level Evidence from Deep Trade Agreements

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…TBTs consist of both voluntary and mandatory measures for achieving product standards, and in the case of food products, encompass labelling specifications, nutrition requirements, stipulations on quality, and packaging conditions (WTO, 2022d). 4 Another recent and noteworthy development in the global trading system has been the concerted trend towards the regulatory convergence/harmonisation of SPS measures and TBTs within PTAs (Fernandes et al, 2021;Santeramo & Lamonaca, 2022b). Regulatory convergence can take several forms, and in general, such provisions relate to requirements on mutual recognition (PTA signatories agreeing to uphold the standards of their fellow members), equivalence (signatories agreeing to treat their fellow members' standards as equivalent to their own), or explicit harmonisation (the adoption of consistent and harmonised standards by all PTA members) of SPS measures and/or TBTs.…”
Section: Introductionmentioning
confidence: 99%
“…TBTs consist of both voluntary and mandatory measures for achieving product standards, and in the case of food products, encompass labelling specifications, nutrition requirements, stipulations on quality, and packaging conditions (WTO, 2022d). 4 Another recent and noteworthy development in the global trading system has been the concerted trend towards the regulatory convergence/harmonisation of SPS measures and TBTs within PTAs (Fernandes et al, 2021;Santeramo & Lamonaca, 2022b). Regulatory convergence can take several forms, and in general, such provisions relate to requirements on mutual recognition (PTA signatories agreeing to uphold the standards of their fellow members), equivalence (signatories agreeing to treat their fellow members' standards as equivalent to their own), or explicit harmonisation (the adoption of consistent and harmonised standards by all PTA members) of SPS measures and/or TBTs.…”
Section: Introductionmentioning
confidence: 99%
“…Technical regulations can significantly facilitate or hinder trade [8] based on the specific products or markets that enter the data. Some studies suggest a negative effect of technical measures on trade ev en though the intensity of such effect varies across products [9][10][11][12][13] while others found both positive and negative effects on trade [4,8,14,15]. This heterogeneity leads to a new field of research that aims at laying a theoretical foundation explaining the mechanics of technical measures' effect on trade.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the trade effects of the overall depth of RTAs and demonstrated that an increase in the depth of RTAs has a positive impact on traditional trade [ 2 , 3 ], value chain trade [ 4 , 5 , 6 , 7 ], and the value chain division of labor [ 8 , 9 ]. Meanwhile, some scholars have researched the trade effects of the depth of the terms in RTAs and examined the heterogeneous impacts of the depth of environmental terms [ 10 , 11 ], the depth of digital trade facilitation terms [ 12 ], the depth of intellectual property terms [ 13 ], and the depth of technical trade measures terms [ 14 ] on a country’s foreign trade. Second, regarding the factors affecting residents’ health, scholars have mainly analyzed the internal and external factors that affect residents’ health.…”
Section: Introductionmentioning
confidence: 99%